2008
DOI: 10.1016/j.ejcts.2008.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, associated factors and evolution of non-severe functional mitral regurgitation in patients with severe aortic stenosis undergoing aortic valve replacement

Abstract: The presence of intermediate degree mitral regurgitation in patients undergoing isolated aortic valve replacement increases morbidity and mortality. However, a high percentage of those who do survive experience disappearance or improvement of the mitral regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 17 publications
6
54
1
6
Order By: Relevance
“…[1][2][3]6,7 The findings of the present analysis, performed on the as-treated population of cohort A of the PARTNER trial, add considerably to the understanding of the impact of moderate/severe MR in high-risk patients undergoing isolated TAVR and SAVR. Importantly, improvements in symptoms and functional class were found with both TAVR and SAVR, regardless of the severity of MR.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]6,7 The findings of the present analysis, performed on the as-treated population of cohort A of the PARTNER trial, add considerably to the understanding of the impact of moderate/severe MR in high-risk patients undergoing isolated TAVR and SAVR. Importantly, improvements in symptoms and functional class were found with both TAVR and SAVR, regardless of the severity of MR.…”
Section: Discussionmentioning
confidence: 99%
“…the role of functional etiology as a predictor of Mr improvement after taVr is highlighted by toggweiler et al 12 in a study on 478 patients. depressed lV ejection fraction and larger lV diameters have also been associated with better improvement of Mr 7,25,26,27 , while calcific degeneration of mitral valve 25 , atrial fibrillation, large left atrial size and pulmonary arterial hypertension have been found to be associated with lack of improvement in Mr after aVr 6,28,29,30 . Furthermore, a 2010 study by Matsumura et al 31 identified preoperative tenting area, tenting height and mitral annulus area -measured by standard echocardiography -as independent predictors of persistent Mr after aVr.…”
Section: Impact Of Avr On Concomitant Mr: Is There An Improvement?mentioning
confidence: 99%
“…Легкая сте-пень MН у больных с первичным дегенеративным пора-жением клапана хорошо компенсируется в течение мно-гих лет, однако даже незначительная функциональная MН, особенно у больных с низкой фракцией выброса, имеет негативное прогностическое значение. Ряд данных свидетельствует о том, что наличие промежуточных сте-пеней МН после протезирования АК значительно ухуд-шает отдаленные результаты лечения [13,61,71,79].…”
unclassified
“…В то же время, согласно некоторым данным [13], после протезирования АК митральная недостаточность снижает-ся в среднем лишь на 50%. Это наблюдение свидетельствует в пользу агрессивного подхода с сопутствующей пластикой МК при ПАК.…”
unclassified
See 1 more Smart Citation